Electrodynamic sensor for determining the state of water in biological objects - Liu, Chang; Bondarenko, I.N.; Panchenko, A.Yu.; Slipchenko, N.I. (Radiotekhnika, 2018)
The distribution of free water and water associated with molecules of biological matter determines its state. The electrophysical properties of free and bound water are significantly different, and the relaxation frequency of molecules lies in the microwave range. Therefore, microwave methods of measurement are effective. The microwave sensor circuit is analyzed, for which it is possible to create a rigorous analytical model. The results of calculations of the electromagnetic field components and the transfer function of the sensor are discussed, and the dimensions of its working area are estimated.